Are Sportive Games Affecting the Lipid Profile in Adolescents? - Çınar, Vedat; Akbulut, Taner; Pancar, Zarife; Kılıç, Yakup (My University, 2019)
The purpose of this study was to investigate the effects of sportive games on the lipid profile in some selected branches for tenweeks applied to adolescents. 11-14 age range; A total of 52 children, 26 in the study group and 26 in the control group,participated voluntarily in research. While the participants in the control group were only attending physical education lessons,participants in the research group played sport games for ten weeks, three times in a week, 60 minutes in a day differentbranches. Blood samples were taken from both groups two times before and after ten weeks of the program. Cholesterol,Triglyceride, HDL, LDL and VLDL cholesterol levels of were determined in taken blood samples. The obtained data wereanalyzed in the SPSS 22.0 Package program. Independent samples t test was used to determine differences between groups, andPaired samples t test was used to determine intra-group differences. When the pretest values of the participants werecompared, there was no difference between the groups in the values of Cholesterol, Triglyceride, HDL, LDL and VLDLCholesterol (p>0.05), HDL cholesterol levels were different in favor of the study group when the post test values werecompared. In the intra-group evaluations, there was no difference between the pre-post tests values of the control group, it wasdetermined that the research group had differences in the levels of cholesterol and HDL cholesterol (p<0.05). As a result,sportive games that applied throughout ten weeks to adolescents had positive effects on lipid profile, it can be said that theymay have a health promoting role if they are made permanent.
Keywords: Beslenme ve Diyetetik; Spor Bilimleri